Glaubensbekenntnis oder Sklavengehorsam? Petrus von Alexandrien zu einem christlichen Dilemma - Vaucher, Daniel (2018)
The so-called Canonical letter (or περὶ Μετανοίας, "On Repentance") of St. Peter of Alexandria, sheds light on a variety of means that Christians chose to avoid the sacrifice test under the Diocletian persecution. Canons 5-7 deal explicitly with slave- owners using their slaves as surrogates. St. Peter condemns these practices heavily, while at the same time he condemns servile obedience. In this, Peter is almost alone in early Christianity, when almost all Christians preached blind obedience. The article examines these canons, and contextualizes them with other Christian perceptions of ancient slavery. At the same time, the letter is important for the understanding of the Great persecution, its mechanisms, and the personal situation of St. Peter. Hence, the letter is discussed in regards to its transmission, and its context.
Keywords: Early Christianity; Persecutions; Peter of Alexandria; Repentance; Slavery